Phase change and aerogel dual functionalized composites materials with double network structure through one-step preparation of polyacrylamide/calcium alginate/polyethylene glycol. (3rd May 2021) - Liu, Lingwei; Zou, Xinquan; Wang, Yuanzhen; Zhou, Weidong; Shi, Junfeng; Ye, Yongming; Zhao, Yunhe; Zhang, Hong; Yu, Yue; Guo, Jing; Xia, Ying
Abstract: The cross-linked polyacrylamide (PAM)/calcium alginate (CA)/polyethylene glycol (PEG) phase change aerogel (PCA) with double network (DN) structure was prepared by emulsion polymerization for thermal energy management. The PCA retained the original porous structure of the aerogel combined with high phase change latent heat and achieved the dual functions of phase change material (PCM) and aerogel. The analysis of BET revealed that porosity and BET specific surface area of PCA were 71.9% and 230 m 2 /g, respectively. The pore size distribution of PCA was between 1.73 and 9.13 nm. The melting enthalpy and crystallization enthalpy of the PCA based on differential scanning calorimetry (DSC) results were 91.5 J/g at 37.9 °C and 89.8 J/g at 37.3 °C, respectively. The PCA exhibited good thermal reliability and stability based on the thermogravimetric analysis (TGA) curve and the thermal cycle test. Graphical abstract: Image 1 Highlights: The synthesized phase change aerogel (PCA) achieves the dual functions of phase change materials and aerogel. The synthesized PCA presents good stability in chemical and morphological structure after thermal cycling. The PEG is immobilized in the porous skeleton of PCA by a double network interlocking structure.